A New Religious Identity in The Age of Cyber Culture : (Instagram Account Family Content Study) - Dwi Sri Handayani (Islamic Studies Journal for Social Transformation, 2023)
The rapid development of the digital world began to penetrate into almost all areas of people's lives to bring various issues and cases around digital society which later developed into a cyberculture. Cyber culture itself is inseparable from human behavior towards technology both in the social, economic, and lifestyle fields. The use of media access makes it easier to form information and social telecommunications such as content on Instagram accounts. It is undeniable that easy access also causes a lot of addiction, moral degradation, deviation and various other things. The suitability of content as an external factor will filter the human mind internally and will produce appropriate behaviors if implemented. Although each content has its own characteristics and intentions in its creation, it is inseparable from content related to religion and family if managed properly, it becomes a good reflection or example. This study wants to examine (1) The clustering of these media accounts when viewed from the current era, and (2) Looking at the new religious identities that emerge from the family's media content. This research is a type of content analysis that is carried out systematically by looking at the content of written or printed information in mass media. Data collection is carried out by observation and documentation. Meanwhile, the analysis was carried out using qualitative descriptive analysis by looking at field data and also the appropriate theory in this study. The results of this study describe the typology on family media accounts on Instagram. Then also a new religious identity in the scope of the public sphere, namely knowledge sharing and Muslim consumerism.